2008
DOI: 10.1002/prot.22063
|View full text |Cite
|
Sign up to set email alerts
|

Isoform‐specific variation in the intrinsic disorder of troponin I

Abstract: Various intrinsic disorder (ID) prediction algorithms were applied to the three tissue isoforms of troponin I (TnI). The results were interpreted in terms of the known structure and dynamics of troponin. In line with previous results, all isoforms of TnI were predicted to have large stretches of ID. The predictions show that the C-termini of all isoforms are extensively disordered as is the N-terminal extension of the cardiac isoform. Cardiac TnI likely belongs to the group of intrinsically disordered signalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 78 publications
(150 reference statements)
0
12
0
Order By: Relevance
“…These observations coincide with the finding that this interhelical turn region was shown to possess a significant degree of “conformational plasticity”, which may play an important role in the function of p85 [ 156 ]. The presence of high levels of intrinsic disorder in the iSH2 domain of PIK3R2 is expected, since the structure formed by this domain is known as a coiled-coil dimer, and since coiled-coil regions in proteins are typically predicted as intrinsically disordered (and are indeed disordered, when dimers are not formed) [ 161 , 162 , 163 , 164 , 165 , 166 ].…”
Section: Resultsmentioning
confidence: 99%
“…These observations coincide with the finding that this interhelical turn region was shown to possess a significant degree of “conformational plasticity”, which may play an important role in the function of p85 [ 156 ]. The presence of high levels of intrinsic disorder in the iSH2 domain of PIK3R2 is expected, since the structure formed by this domain is known as a coiled-coil dimer, and since coiled-coil regions in proteins are typically predicted as intrinsically disordered (and are indeed disordered, when dimers are not formed) [ 161 , 162 , 163 , 164 , 165 , 166 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some of the illustrative examples include: the AS-driven generation of two non-functional variants of the sodium channel SCN5A (which, in the norm, controls cardioprotection by ischemic preconditioning) during heart failure (Shang et al, 2007 ); downregulation of the AS variant of the cell-cycle-regulated kinase (CCRK, which promotes cardiomyocyte growth and survival) in heart failure (Qiu et al, 2008 ); production of the AS variants of the troponin I gene that reduce contraction efficiency (Feng and Jin, 2010 ); and appearance of the AS-generated titin isoforms affecting the cardiac stiffness in individuals with dilated cardiomyopathy (DCM) (Makarenko et al, 2004 ); and the improvement of cardiac function after infarction by the CnAβ 1 AS variant of the phosphatase calcineurin (Felkin et al, 2011 ). Curiously, troponin I (Hoffman and Sykes, 2008 ), titin (Ma et al, 2006 ), and calcineurin (Dunker et al, 2001 ) are all known to possess functionally important IDPRs.…”
Section: Wrecked Regulation Of Idps and Diseasementioning
confidence: 99%
“…Earlier, troponin I was shown to possess functionally important disordered regions (Hoffman et al, 2006 ). Furthermore, subsequent comprehensive bioinformatics analysis revealed that different troponin I isoforms are characterized by different abundance and distribution of intrinsic disorder (Hoffman and Sykes, 2008 ). This isoform-specific disorder variability was suggested to have potential mechanistic significance being responsible for modulation of the extent to which conformational fluctuations in tropomyosin are communicated to the troponin complex (Hoffman and Sykes, 2008 ).…”
Section: Wrecked Regulation Of Idps and Diseasementioning
confidence: 99%
“…The premise that function follows structure has been left behind. A particular example is subunit I of the troponin complex (Hoffman and Sykes, 2008 ; Julien et al, 2010 ). TnI has IDRs with degrees of conformational flexibility that directly impact biological effects, mostly by changing the conformation and function of its partner, the TnC.…”
Section: Allosteric Communication Defines the Hierarchy Of Functionalmentioning
confidence: 99%